Association Between Fast Food Consumption and Overweight Status Among Adolescents - Surya Anita; Dewi R Bancin; Friska Sitorus; Elisa Silvia Aritonang (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Adolescent obesity is a growing national and international public health concern. The rising incidence of overweight in school-age children is believed to be caused by dietary shifts toward fast food, which is heavy in energy, fat, and sugar. Teenagers are more likely to eat fast food because of factors such as availability, convenience, and the influence of media and social surroundings. Such eating patterns may eventually increase the risk of obesity and non-communicable diseases by causing an energy imbalance. As a result, it's critical to determine the relationship between the prevalence of overweight among teenagers and fast-food intake. The purpose of this study was to investigate the association between junior high school students' fast-food consumption and overweight status. However, there is still little data on this connection among teenagers in Indonesia. Methods: A sample of 130 junior high school pupils was chosen using proportionate stratified random sampling in this cross-sectional study. Questionnaires were used to collect data on fast food consumption, and Body Mass Index for Age (BMI-for-age) was calculated using height and weight measurements to assess nutritional health. The Chi-Square test and odds ratios (ORs) with 95% confidence intervals (CIs) were used for data analysis. Results: The prevalence of overweight in this study was 20.0%. The analysis found a strong correlation between fast-food consumption and overweight status (p=0.004). Adolescents who consumed more fast food were more likely to be overweight than those who consumed less (OR = 3.43; 95% CI: 1.44–8.19). Conclusion: High fast-food intake was significantly associated with higher odds of being overweight among junior high school students. May be considered while creating strategies to combat obesity. Strategies for managing teenage obesity could include reducing fast-food consumption.